Metabolic syndrome‐related SNPs in HLA and TNF7L2 may be risk factors for generalized pustular psoriasis in Chinese Han population. Issue 2 (2nd May 2021) - Liu, Y.; Cui, Z.‐Y.; Bao, J.; Zhang, X.‐L.; Guo, Y.; Su, M.‐J.; Han, J.‐W.
Abstract: Background: Generalized pustular psoriasis (GPP) is a rare and severe type of psoriasis. Previous studies have reported that metabolic syndrome and its components have been associated with psoriasis. Objective: To investigate the association of metabolic syndrome‐related single‐nucleotide polymorphisms (SNPs) and GPP in Chinese Han population. Materials and Methods: One hundred and thirty‐six (136) GPP patients and 965 healthy controls were recruited in the study. Approximately, 4 ml peripheral venous blood was collected from each participant. After collection, second‐generation sequencing was used to detect genetic polymorphism of 15 SNPs. The plink 1.07 software package was used for statistical analysis. Results: Rs805303 ( p  = 0.01, OR = 0.70) and rs3177928 ( p  = 3.18E−07, OR = 2.66) in HLA were significantly different between the two groups. Moreover, rs4506565 ( p  = 1.41E−03, OR = 2.72) and rs7901695 ( p  = 9.39E−04, OR = 2.82) in TCF7L2 were significantly associated with GPP in patients without a previous history of PsV. Genotype analysis of rs4506565 and rs7901695 showed that under the recessive model, genotype frequencies of rs4506565 ( p  = 0.00, OR = 18.52) and rs7901695 ( p  = 0.00, OR = 18.44) were significantly different between GPP patients and healthy controls. Conclusion: Rs805303 and rs3177928 in HLA may increase the risk of GPP in the Chinese Han population. TCF7L2 may be a risk factor for GPP in patients without a previous history of PsV. Abstract :